Detailed Experimental and Model-Based Analysis of a Swash-Plate Piston Expander for ORC Application - Oudkerk, Jean-François; Lemort, Vincent (Frontiers in Energy Research, 2020)
A 195 cm3 swash-plate piston expander was tested in an ORC using R245fa as working fluid. Rotational speeds ranging from 1,000 to 4,000 RPM and pressure ratios from 7 to 12 were imposed. In total, 65 steady state points were measured. With these measurements, performance maps were generated to point out the influence of rotational speed and levels of pressure on mechanical power and isentropic efficiency. These maps have highlighted the existence of an optimal rotational speed of around 3,000 RPM maximizing the mechanical power, while the speed that maximizes the isentropic efficiency lies between 2,000 and 2,500 RPM. The maximal mechanical power and isentropic efficiency were 2.8 kW and 53%, respectively. Then the measurements were used to analyze the losses. This analysis has shown that, under the expansion and compression limit, the theoretical isentropic efficiency has values comprised between 90 and 70% for pressure ratios of 7–12. The filling factor affects the isentropic efficiency for low rotational speeds and low pressure ratios. Indeed, indicated isentropic efficiency is around 60% for 1,000 RPM and around 75% for 4000 RPM. These values stay quite constant with the pressure ratio. Finally, a mechanical efficiency comprised between 40 and 90% was observed, which lowers the isentropic efficiency to values comprised between 30 and 53%. Finally, a model based on energy and mass conservation inside a cylinder volume was successfully calibrated and was able to predict mass flow rate, mechanical power, and exhaust temperature with good agreement. This model has enabled disaggregation of the influence of pressure drops and leakages on the filling factor, then on the isentropic efficiency. This analysis has shown that pressure drops mainly affect the compactness of the expander, and not so much the isentropic efficiency (except for low rotational speeds where pressure drops can lower the isentropic efficiency by 14%). In contrary, leakages have a strong impact. The importance of the different sources of losses varies with the speed. For the optimal speed of 2,500 RPM, under-expansion and compression have the strongest impact, followed by mechanical losses, leakages and pressure drops, respectively.